Participatory plant breeding in diverse production environments and institutional settings: Experience of a nepalese NGO - Subedi, A.; Joshi, Krishna D.; Rana, Ram B.; Subedi, Madu (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
This paper provides an overview of participatory plant-breeding (PPB) programs implemented by LI-BIRD in different environments and institutional settings in an attempt to address various breeding goals, such as productivity increase, research efficiency, biodiversity enhancement and on-farm conservation, users' needs, capacity building, and policy changes. It draws lessons from these experiences and raises some concerns about strengthening PPB in the future.